Best Practices: Collaboration to Prevent The Transmission Covid-19 in Jambangan Spesial Region Yogyakarta - Subiyanto Paulus; Widyastuti L (Institute of Computer Science (IOCS), 2021)
There were 8 effective efforts to prevent the spread of the Covid-19: 1) activating the performance of the hamlet andvillage task force; 2) tracing the Covid-19 transmission with a rapid test and continued with PCR Swab for those who are reactive;3) self-isolation for citizens who were confirmed positive; 4) spraying disinfectant in the houses of citizens who were confirmed positive; 5) the application of the behaviors of wearing masks, washing hands, maintaining distance, avoiding crowds, and increasing body immunity; 6) support of local citizens to meet the needs of citizens who must self-isolation; 7) put up banners to prevent the transmission of the Covid-19 at every entrance to the hamlet; 8) installation of hand washing facilities in most of the citizens' houses, in public places, and at each hamlet entrance.